Plurality of actors dan co-coordination sebagai pondasi inovasi GASPOL Kampung KB di Kabupaten Sleman - Noor Azizah Maharani; Bintoro Wardiyanto; Erna Setijaningrum (Riviera Publishing, 2025)
The GASPOL (Joint Movement of Regional Apparatus, Organizations, and Institutions) innovation in the Quality Family Village (KB) of Sleman Regency is a strategic effort by the local government in strengthening collaborative and sustainable public service governance. This innovation is motivated by various problems in the implementation of KB Villages, such as weak cross-sector coordination, fragmentation of programs between agencies, and inequality of capacity and roles between actors involved. This study aims to analyze the implementation of GASPOL innovation through the perspective of New Public Governance (NPG), with an emphasis on the aspects of plurality of actors, co-coordination, and co-production in the implementation of public services. The research method used is a qualitative approach with literature study techniques and analysis of official documents, including regional policies, program reports, and regulations related to KB Villages. The results of the study show that GASPOL is able to build a collaborative network involving regional apparatus, community institutions, village governments, KB Village working groups, and the community as co-producers in the planning and implementation of the program. This collaboration encourages program integration, improved service efficiency, and strengthens community participation. However, the implementation of GASPOL still faces challenges in the form of potential power imbalances between actors, complex coordination, and the risk of program overlap. This study confirms that GASPOL represents the real practice of the New Public Governance paradigm and has the potential to become a model of collaborative governance innovation that can be replicated in other regions.